"I worry about this patient EVERY day": Geriatrics Clinicians' Challenges in Caring for Unrepresented Older Adults. (April 2022) - Dassel, Kara B.; Edelman, Linda S.; Moye, Jennifer; Catlin, Casey; Farrell, Timothy W.
Unrepresented older adults are at risk for adverse outcomes, and clinicians who care for them may face ethical dilemmas and unique challenges when making person-centered care recommendations. However, little is known about their perspectives on clinical challenges in caring for this population. An online survey was used to assess issues around providing care for unrepresented patients. Ninety-two American Geriatrics Society members working with older adults in inpatient and/or outpatient settings completed the survey. Descriptive qualitative analysis of narrative survey responses identified five broad themes: (a) health risk characteristics of patients, (b) care decisions facing the team, (c) psychosocial considerations by the team, (d) patient outcomes, and (e) burden of the provider and/or health system. These findings demonstrate that geriatrics clinicians face challenges in working with unrepresented adults in both inpatient and outpatient settings. We interpret these results in light of existing literature and propose collaborative approaches that may improve outcomes.